Modifiable risk factors control post coronary artery bypass graft (CABG) and its coronary events within 5 years at Hospital USM: A retrospective cohort review - Ismail, Mohamad Zikir (2023)
Patient post CABG are at high risk of developing another heart attack that require graft study and coronary angioplasty. These are common after 10 years post operation due to graft occlusion. Even though at 5 years post CABG, graft patency are excellent as reported by many studies (See et al., 2020), patients still can get coronary events earlier than expected if modifiable risk factors control are not well optimized according to guidelines. Modifiable risk factors which are diabetes mellitus, hypertension, hyperlipidemia and active smoking play an important role and contribue to early graft failure. Therefore, this study aim to determine incidence rate of coronary events, to describe the status of modifiable risk factors control and also to look for any association between each modifiable risk factors towards coronary events within 5 years post CABG. Methodology This is retrospective cohort review study that involve 135 patients post CABG who had the operation done from 01 Januari 2011 until 31 December 2017 in Hospital USM. Information and data regarding sex, age, race and underlying relevant medical illness are recorded. 5 years data of modifiable risk factors which are diabetes mellitus, hypertension, hyperlipidemia and smoking status also identified. Coronary events which are acute coronary syndrome or angioplasty that were occurred within 5 years post CABG also identified. All of these data were recorded in patient performa then were transferred to excel sheet for data analysis. Results A total of 135 patients that underwent CABG in Hospital USM and fulfilled criteria for this study were identified. From data analysis, 19 patients (14%) experienced at least one acute coronary syndrome within 5 years post CABG. None of patient underwent angioplasty, and all of them treated medically. The status of modifiables risk factors control which are blood pressure, LDL, TG and Hba1c showed that they are not well controlled and optimized as per guidelines. Cumulatively within 5 years, 46.6% of patients had uncontrolled systolic blood pressure (M=149.01 SD=12.7) and 18.5% had uncontrolled diastolic blood pressure (Mean=87.55, SD=6.7). 96% patients had uncontrolled LDL (Mean=3.08, SD=0.9). Other cholestrol component TG showed 49% had uncontrolled TG (Mean=2.32, SD=1.3) throughout 5 years. For glycemic control, 53% of patients had uncontrolled HbA1c (Mean=9.36, SD=1.4). In addition, the result showed 95% of patients were remained off ciggarettes within 5 years post CABG ). Lastly our study showed significant association between TG, HbA1C, smoking status and acute coronary syndromes. Conclusion Our study showed that in first 5 year post CABG, incidence rate of coronary events is low which is 2.8 cases per 100 person years. We also found that all the coronary events which were acute coronary syndrome are treated medically without the need to repeat coronary angioplasty. The status of modifiables risk factors control which are blood pressure, LDL, TG and Hba1c show that they are not well controlled and optimized as per guidelines. The modifiable risk factors which are Hba1c, blood pressure and TG were significantly associated with acute coronary syndromes.